2021
DOI: 10.1093/noajnl/vdab146
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoresistant seizures and IDH mutation in low-grade gliomas

Abstract: Purpose Many low-grade gliomas (LGG) harbor isocitrate dehydrogenase (IDH) mutations. Although IDH mutation is known to be epileptogenic, the rate of refractory seizures in LGG with IDH mutation vs wild-type had not been previously compared. We therefore compared seizure pharmacoresistance in IDH-mutated and wild-type LGGs. Methods Single-institution retrospective study of patients with histologic proven LGG, known IDH mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
10
1
Order By: Relevance
“…Importantly, SCRAM predicted the existence of these neuronal-like tumor cells as a defining feature of IDH1 mut tumors representing nearly half of tumor cells in our human datasets, which we confirmed experimentally. Notably, IDH1 mut glioma frequently presents with seizures 45 despite a slower disease course, raising the possibility that these neuronal-like cell types may contribute to hyperexcitable phenotypes that present clinically. Future investigations may aim to better define the electrophysiological contributions of these cells to tumor progression and may seek to characterize how modulation of electrophysiological activity originating from tumor cells alters disease outcomes in glioma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, SCRAM predicted the existence of these neuronal-like tumor cells as a defining feature of IDH1 mut tumors representing nearly half of tumor cells in our human datasets, which we confirmed experimentally. Notably, IDH1 mut glioma frequently presents with seizures 45 despite a slower disease course, raising the possibility that these neuronal-like cell types may contribute to hyperexcitable phenotypes that present clinically. Future investigations may aim to better define the electrophysiological contributions of these cells to tumor progression and may seek to characterize how modulation of electrophysiological activity originating from tumor cells alters disease outcomes in glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, NLTs were the only cells expressing proliferation markers in our Patch-seq dataset, suggesting that NLTs are important contributors to both the neurophysiological and proliferative characteristics of glioma. Clinically, IDH1 mut glioma frequently presents with seizures 58 , raising the possibility that NLTs may contribute to both hyperexcitable and proliferative phenotypes in these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Patients affected by IDH mutant gliomas present a more frequent epileptic activity compared to IDH wildtype patients [88] [89]. Unfortunately, the seizures showed by IDH mutant patients are frequently resistant to first line epilepsy treatment [90]. Nevertheless, recently it has been reported that a patient affected by IDH1 mutant oligodendroglioma showed reduced tumor-associated epilepsy after treatment with the IDH1 mutant inhibitor AG-120 (ivosidenib) [91].…”
Section: Idh Mutation and Tumour-associated Epilepsymentioning
confidence: 99%
“…Patients with IDH mutated grade 2 gliomas are much more likely to experience medication-refractory seizures than IDH wt grade 2 patients. Within the group of IDH wt tumors [10], grades 2 and 3 tumors are more likely to present with early seizures, have more seizure days, and require more often polytherapy than IHD wt glioblastomas [11].…”
Section: Etiologymentioning
confidence: 99%